FOA: a meta heuristic approach for load balancing in cloud computing - Mohanty, Subhadarshini; Patra, Prashanta Kumar; Ray, Mitrabinda (International Journal of Engineering and Technology, 2018)
Cloud computing is a distributed computing framework that provides computational facilities, where information and assets are recovered from cloud service provider via the web, by means of a well-framed online application. But, resource sharing often leads to unavailability of resources, resulting in a deadlock situation. One approach to avoid this is by disseminating the workload uniformly between the encumbered and idle machines. This is called load balancing. The aim of doing this is to reduce the average response time and maximize resource utilization. Forest Optimization Algorithm (FOA) is based on governance of trees in the forest and survival of distinct trees. These trees have proper geological and developing conditions. The proposed Algorithm is an attempt to find these distinguished solutions from the pool to avoid starvation of tasks, at the same time improving the average response time by utilizing the process of seed dispersal in forests.